PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN DARING DALAM MASA PANDEMI COVID 19 DI STIKES BAITURAHIM JAMBI - Fithriyani, Fithriyani; Vevi Suryenti Putri (JOEL: Journal of Educational and Language Research, 2022)
Corona Virus or known as COVID-19 has now spread to various countries in the world. COVID-19 is reported to be quite contagious with a relatively high mortality rate and is reported to continue to increase. The number of positive COVID-19 patients that continues to grow in Indonesia has forced education units to follow government regulations for the implementation of online lectures which is a national policy as a strategic step in efforts to prevent the spread of the COVID-19 virus. The purpose of the study was to determine student perceptions of online learning during the 2019 covid pandemic at Baiturahim High School of Health, Jambi. The design of this study is a quantitative research with a descriptive analytic design. The sampling technique was purposive sampling to students of the nursing undergraduate study program. The activeness and readiness of students to take online lectures 49.5% agree with online lectures, the most widely used media during online lectures is YouTube as much as 37.8%, effective learning media during online lectures using the zoom application is 37.1%, learning styles visual interest, the 2-way communication model is 54.5% such as video conferencing (zoom) and the effectiveness of online lectures is not satisfied that is 32.2% and satisfied is 31.5%. Students' perceptions of online learning during the covid pandemic are mostly good, although with various obstacles during online lectures. It takes the role of universities to provide facilities and infrastructure that support the implementation of online lectures during a pandemic.